A novel GJA8 mutation is associated with autosomal dominant lamellar pulverulent cataract: further evidence for gap junction dysfunction in human cataract. Issue 1 (5th January 2006) - Arora, A; Minogue, P J; Liu, X; Reddy, M A; Ainsworth, J R; Bhattacharya, S S; Webster, A R; Hunt, D M; Ebihara, L; Moore, A T; Beyer, E C; Berthoud, V M
Abstract : Purpose: To identify the gene responsible for autosomal dominant lamellar pulverulent cataract in a four-generation British family and characterise the functional and cellular consequences of the mutation. Methods: Linkage analysis was used to identify the disease locus. The GJA8 gene was sequenced directly. Functional behaviour and cellular trafficking of connexins were examined by expression in Xenopus oocytes and HeLa cells. Results: A 262C>A transition that resulted in the replacement of proline by glutamine (P88Q) in the coding region of connexin50 (Cx50) was identified. hCx50P88Q did not induce intercellular conductance and significantly inhibited gap junctional activity of co-expressed wild type hCx50 RNA in paired Xenopus oocytes. In transfected cells, immunoreactive hCx50P88Q was confined to the cytoplasm but showed a temperature sensitive localisation at gap junctional plaques. Conclusions: The pulverulent cataract described in this family is associated with a novel GJA8 mutation and has a different clinical phenotype from previously described GJA8 mutants. The cataract likely results from lack of gap junction function. The lack of function was associated with improper targeting to the plasma membrane, most probably due to protein misfolding.